ANALISIS STRATEGI MENYEDERHANAKAN MASALAH SERUPA DAN SUDUT PANDANG LAIN PADA PERMASALAHAN NON RUTIN PENJUMLAHAN FUNGSI - Kartika Maharani Dwi Astuti; Rubono Setiawan (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2017)
The problem of Addition Operation of Functions often emerges in Junior National Science and Math Olympiads at the regional level, provincial level, and national level. Non-routine questions related to the addition of functions tested In the Junior National Science Math Olympiad are more concern on the problem-solving. The questions have complex types and these types cannot directly solved by common routine procedures. Systematic-logical thinking and high level of understanding ability are required to solve the problem. There are some basic strategies which can be implemented to find the right solutions. Blended strategy plays a significant role to solve the problem. This research will discuss about the strategy to simplify equal group problem from another point of view in order to solve the addition of functions problem in the Junior National Science Math Olympiad. The implementation of the strategy is based on the Polya’s Problem-Solving Techniques.